Tingkat penggunaanCT-scanuntukpemeriksaanameloblastoma di RS Wahidin Sudirohusodo lebih tinggi dibandingkan dengan radiografi konvensional Level of using CT-scan in examinating ameloblastoma at Wahidin Sudirohusodo Hospital was higher than conventional radiographies - Syamsiar Toppo (DiscoverSys Inc., 2013)
Radiographies are commonly used in dentistry. One of them is CT-scan. CT-scan is used in a variety of cases, particularly in the oral cavity to detect the presence of ameloblastoma. This study aimed to determine the prevalence ofusing CT-scan at Wahidin Sudirohusodo Hospital to examinate ameloblastoma descriptive observationally using crosssectional study. This research is the base study by collecting data of the patients took x-ray, from the patients’ dentalrecord at the Installation of Medical Records in 2012. Then, the results are distributed into tables and presented bygraphic. Data showed that ameloblastoma patients examinated with CT-scan are 55 patients (83.3%) and otherconventional x-ray are 11 patients (16.7%) of the total 66 patients. It was concluded that the level of using CT-scan forexamination of ameloblastoma in the Hospital was higher than other conventional radiographies.